2020
DOI: 10.3390/biom10030428
|View full text |Cite
|
Sign up to set email alerts
|

Salient Features of Monomeric Alpha-Synuclein Revealed by NMR Spectroscopy

Abstract: Elucidating the structural details of proteins is highly valuable and important for the proper understanding of protein function. In the case of intrinsically disordered proteins (IDPs), however, obtaining the structural details is quite challenging, as the traditional structural biology tools have only limited use. Nuclear magnetic resonance (NMR) is a unique experimental tool that provides ensemble conformations of IDPs at atomic resolution, and when studying IDPs, a slightly different experimental strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 110 publications
1
19
0
Order By: Relevance
“…In 1996, Weinreb et al observed that Wild-Type (WT) αSyn exists in solution as a dynamic ensemble of conformations lacking a single equilibrium structure and, therefore, classified it as an IDP ( Weinreb et al, 1996 ). Many studies have advanced our knowledge in this field by applying experimental (for a recent review on NMR investigations see Kim et al, 2020 ) and computational (e.g., MD, Monte Carlo simulations) techniques ( Jónsson et al, 2012 ), or a combination of both approaches ( Brodie et al, 2019 ). However, due to αSyn structural heterogeneity that depends on many different biological and physico-chemical factors ( Stephens et al, 2019 ), caution is needed when interpreting these results.…”
Section: Monomeric Wild Type (Wt) αSyn Structural Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1996, Weinreb et al observed that Wild-Type (WT) αSyn exists in solution as a dynamic ensemble of conformations lacking a single equilibrium structure and, therefore, classified it as an IDP ( Weinreb et al, 1996 ). Many studies have advanced our knowledge in this field by applying experimental (for a recent review on NMR investigations see Kim et al, 2020 ) and computational (e.g., MD, Monte Carlo simulations) techniques ( Jónsson et al, 2012 ), or a combination of both approaches ( Brodie et al, 2019 ). However, due to αSyn structural heterogeneity that depends on many different biological and physico-chemical factors ( Stephens et al, 2019 ), caution is needed when interpreting these results.…”
Section: Monomeric Wild Type (Wt) αSyn Structural Featuresmentioning
confidence: 99%
“…Monomeric WT αSyn N-terminal region can adopt different transient secondary structural features in aqueous solution due to its intrinsically disordered nature. Several studies observed a tendency in the αSyn N -terminus to acquire a helical secondary structure ( Vilar et al, 2008 ; Allison et al, 2009 ; Jónsson et al, 2012 ; Coskuner and Wise-Scira, 2013 ; Zhang et al, 2018 ; Bhattacharya et al, 2019 ; Brodie et al, 2019 ; Meade et al, 2019 ; Kim et al, 2020 ). This helical pattern has been proposed to be essential for vesicle and membrane binding ( Coskuner and Wise-Scira, 2013 ; Vasili et al, 2019 ).…”
Section: Monomeric Wild Type (Wt) αSyn Structural Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, two reviews enriched our Special Issue with a wide and extensive discussion on certain topics [ 13 , 14 ]. The review by Sokolik and co-workers gave a structural overview on the fascinating WASp-interacting protein (WIP), which is a regulator of actin cytoskeleton assembly and remodeling, a cellular multi-tasker, and a key member of a network of protein–protein interactions [ 13 ].…”
mentioning
confidence: 99%
“…The authors provided a deeper understanding of the mechanisms by which WIP mediates its biological functions, which have an impact on health and disease, paving the way for a better understanding of key biological processes with potential therapeutic implications. Last, but not least, Kim and coworkers overviewed the features revealed by NMR spectroscopy of monomeric alpha-synuclein, for which the aggregation is strongly correlated with Parkinson’s disease [ 14 ].…”
mentioning
confidence: 99%